Stimulasi Permainan Lompat Tali Terhadap Perkembangan Motorik Kasar Pada Anak Prasekolah - Yustanta, Brivian Florentis (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Stimulation of gross motor development needs to be done from an early age. One of the game that can stimulate gross motor skills is the jump rope game which can help children control body movements correctly and create positive emotions for children so that children do not realize that they are actually practicing gross motor skills. The aim of this research was to determine the correlation between the stimulation of jumping rope games and the development of gross motor skills in preschool children at Assa'diah Early Childhood Education, Bogor Regency. The research design uses correlation analytics with the dependent variable being gross motor ability and the independent variable being stimulation by jumping rope. The population was 43 children. Using simple random sampling, it was found that the sample size was 31 respondents. Data collection on 20 - 25 June 2024 at Assa'diah Early Childhood Education Bogor Regency used observation sheets with chi square test analysis. The research results showed that the respondents' abilities when given the stimulation of the jump rope game were in the very good category (67.7%), while their gross motor development was in the normal category (87.1%). The correlation between the stimulation of jumping rope and gross motor development in preschool children with a p value of 0.011 < 0.05. Based on the research results, there was a correlation between the stimulation of jumping rope games and the development of gross motor skills in preschool children. This shows that good stimulation from jumping rope will have a positive impact on children's gross motor development in the normal category.